(untitled) (Studia Prawnicze / The Legal Studies, 2007)
Międzynarodowy Pakt Praw Obywatelskich i Politycznych przyjęty przez Zgromadzenie Ogólne Narodów Zjednoczonych w dniu 16 grudnia 1966 r. był pierwszym prawnie wiążącym dokumentem wydanym przez Organizację Narodów Zjednoczonych, który nałożył na państwa-strony obowiązek przestrzegania praw osób należących do mniejszości narodowych. Article 27 of the International Covenant on Civil and Political Rights provides that, in those States in which ethnic, religious or linguistic minorities exist, persons belonging to such minorities shall not be denied the right, in community with the other members of their group, to enjoy their own culture, to profess and practise their own religion, or to use their own language. The aim of the author is to prove that Article 27 is in fact widely considered to be the primary provision guaranteeing protection by the UN to persons belonging to minorities. The scope of Article 27 has been subject to many discussions and interpretations. The Humań Rights Committee (HRC) had an important role to play in clarifying the scope and application of the article. The case-law of the HRC has been presented by the author. The terms used in article 27 indicate that the persons designed to be protected are those who belong to a group and who share in common a culture, a religion and/or a language. Those terms also indicate that the individuals designed to be protected need not be citizens of the State party. Moreover, migrant workers or even visitors in a State party constituting such minorities are entitled not to be denied the exercise of those rights. The existence of an ethnic, religious or linguistic minority in a given State party does not depend upon a decision by that State party but reąuires to be established by objective criteria. Although article 27 is expressed in negative terms, that article, nevertheless, does recognize the existence of a „right” and reąuires that it shall not be denied. Moreover, State party is under an obligation to ensure that the existence and the exercise of this right are protected against their denial or yiolation. Positive measures of protection are, therefore, reąuired not only against the acts of the State party itself, whether through its legislative, judicial or administrative authorities, but also against the acts of other persons within the State party. Although the rights protected under article 27 are individual rights, they depend in tum on the ability of the minority group to maintain its culture, language or religion. It has to be observed that such positive measures must. respect the provisions of articles 2.1 and 26 of the Covenant both as regards the treatment between different minorities and the treatment between the persons belonging to them and the remaining part of the population. However, as long as those measures are aimed at correcting conditions which prevent or impair the enjoyment of the rights guaranteed under article 27, they may constitute a legitimate differentiation under the Covenant, provided that they are based on reasonable and objective criteria.